The role of cyclooxygenase-2 (COX-2) and inflammatory markers in the progress of Alport syndrome in Egyptian children - Moushira Zaki; Hisham A. Orban; Mohamed A. Shahba; Rehab S. I. Moustafa; Ahmed Adel; Fatina I. Fadel; Abeer Selim; Hala T. El-Bassyouni; Eman R. Youness (BMC Pediatrics)
Abstract Background Chronic inflammation and its control are crucial to the responses of glomerular and renal tubular cells. This contributes to the pathogenic mechanisms and advancement of the disease in Alport syndrome. The study aimed to elucidate the role of cyclooxygenase-2, Interleukin 4, Plasminogen activating inhibitor 1, and Prostaglandin E2 in the development and course of Alport syndrome. Methods In our study inflammatory markers were evaluated in 26 Alport syndrome patients, 15 males and 11 females and 24 controls. Results Their age ranged from 4 to 16 years (mean ± SD was 8.50 ± 2.877) and 24 were normal controls matching age and sex. The serum levels of cyclooxygenase-2, Prostaglandin E2, Interleukin 4, and Plasminogen activating inhibitor 1 were evaluated in all patients. The serum level of cyclooxygenase-2, Prostaglandin E2, Interleukin 4, and Plasminogen activating inhibitor 1 were all increased significantly in the Alport syndrome patients compared to control (588.68 ± 73.08, 42.57 ± 4.18, 42.32 ± 3.49, and 846.47 ± 45.433, respectively versus controls (369.12 ± 50.28, 25.52 ± 4.98, 28.89 ± 3.19, and 312.79 ± 40.53 respectively). Conclusion The role of inflammatory markers cyclooxygenase-2, Prostaglandin E2, Interleukin 4, and Plasminogen activating inhibitor 1 in Alport syndrome that are causally connected and have a role in the development and course of Alport disease was delineated. This may highlight and speculate an innovative strategy for targeting the creation of safe and efficient anti-inflammatory treatments to inhibit disease progression in Alport syndrome.